The Ultrasonic Pulse Velocity and Lagrangian Approaches to Predict the Effective Thickness and Homogeneity of the Sandwich Panel - Faqih Ma'arif; Slamet Widodo; Maris Setyo Nugroho; Mohamad Tafrikan; Zhengguo Gao (Kadiri University, 2022)
Non-destructive testing can be applied to various things, including sandwich panels. Sandwich panels made of EPS are greatly affected by the mixing process. Bad mixing can affect the level of homogeneity and reduce quality. In addition, the improper thickness of layers and cores can result in wall damage. For this reason, carrying out a non-destructive test on the sandwich panel is necessary. This study aims to determine the homogeneity of the material and predict the dimensions of the EPS core and layer. Experimental testing was conducted using Ultrasonic Pulse Velocity (direct method) with 90 points. The test object consisted of six sandwich panel walls with three variants, each with dimensions and layer thickness of 15 mm, 20 mm, and 25 mm, respectively, while the core layer size was 70 mm, 80 mm, and 90 mm, respectively. The test results were analyzed on travel time and wave velocity using a statistical analysis approach including covariance, Kolmogorov-Smirnov, ANOVA, t-test, and Lagrangian. The analysis results show that the mixture's homogeneity can be determined based on the ultrasonic pulse velocity. The proposed Lagrange analysis can reveal the behavior of the propagation speed. Based on the results of the Lagrange approach, the highest speed is obtained at a thickness of 80 with a maximum speed of 2.395 km/s. The results of this study contribute to the non-destructive test procedure, especially in determining homogeneity and the dimensions of the effective thickness of the structural walls (cores and layers) that have been installed in the field quickly, cheaply, accurately, and briefly.